Examining Hepatitis C Virus Treatment Preference Heterogeneity Using Segmentation Analysis: Treat Now or Defer? - Fraenkel, Liana; Lim, Joseph; Garcia-Tsao, Guadalupe; Reyna, Valerie; Monto, Alexander (Journal of clinical gastroenterology, 2015)
To improve our understanding of patients' treatment preferences for chronic hepatitis C (HCV).